2015
DOI: 10.1186/s11689-015-9133-6
|View full text |Cite
|
Sign up to set email alerts
|

Route knowledge and configural knowledge in typical and atypical development: a comparison of sparse and rich environments

Abstract: BackgroundIndividuals with Down syndrome (DS) and individuals with Williams syndrome (WS) have poor navigation skills, which impact their potential to become independent. Two aspects of navigation were investigated in these groups, using virtual environments (VE): route knowledge (the ability to learn the way from A to B by following a fixed sequence of turns) and configural knowledge (knowledge of the spatial relationships between places within an environment).MethodsTypically developing (TD) children aged 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 42 publications
5
49
1
Order By: Relevance
“…Second, this argument is in line with a recent study which found that seeing a sketch map as well as listening to a description enhanced acquisition of configural knowledge, but the effect was weaker in the DS group than the TD group (Meneghetti et al ., ). It is possible, therefore, that the DS impairment in acquisition of configural knowledge (Courbois et al ., ; Farran et al ., ) is more evident under certain presentation conditions, that is, in the conditions that would enhance TD children's acquisition of configural knowledge.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Second, this argument is in line with a recent study which found that seeing a sketch map as well as listening to a description enhanced acquisition of configural knowledge, but the effect was weaker in the DS group than the TD group (Meneghetti et al ., ). It is possible, therefore, that the DS impairment in acquisition of configural knowledge (Courbois et al ., ; Farran et al ., ) is more evident under certain presentation conditions, that is, in the conditions that would enhance TD children's acquisition of configural knowledge.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, individuals with DS were less able than controls to find new (i.e. not previously trained) shortcuts between two given landmarks (Courbois et al ., ; Farran et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our results dovetail with previous research showing that WS individuals have difficulties navigating in large‐scale spaces and often get lost in unfamiliar environments (Farran, Blades, Boucher, & Tranter, ; Farran et al., ; Foti et al., ). Previous work has shown that WS individuals are especially impaired at place‐based spatial memory tasks (Mandolesi et al., ), but exhibit relatively intact response‐ or route‐based spatial learning (Purser et al., ; but see Farran et al., ), particularly with repeated environmental exposures (Farran, Courbois, Van Herwegen, & Blades, ; Farran et al., ). Indeed, when WS and TD individuals were tested on both place‐based and response‐based memory tasks, the WS individuals were comparatively impaired on the place‐based tasks (Bostelmann et al., ).…”
Section: Discussionmentioning
confidence: 99%